The Effect of Ethnoscience Learning on the Development of Students' Cognitive and Affective Aspects in Junior High School - Hikmawati; I Wayan Suastra; Ketut Suma; A A Istri Agung Rai Sudiatmika; Endang Puji Astuti (Postgraduate, University of Mataram, 2024)
This research aims to examine the influence of ethnoscience learning on the development of students' cognitive and affective aspects. This quasi-experimental research uses a pre-test post-test non-equivalent control group design. This research was carried out in the odd semester of the 2022/2023 academic year. The population of this study was 320 class VII students at MTsN 1 Mataram, with a sample size of 34 people in the experimental class and 34 people in the control class. Data was obtained from test instruments for the